Reduction of venous thromboembolism following prolonged prophylaxis with the low molecular weight heparin Certoparin after endoprothetic joint replacement or osteosynthesis of the lower limb in elderly patients - Kolb, Gerald; Bodamer, Iris; Galster, Heide; Seidlmayer, Christoph; Grambach, Konrad; Koudela, Karel; Eisele, Ralf R.; Becker, Clemens; Paal, Valerie; Spannagel, Uwe; Brom, Joachim; Weidinger, Gottfried (Thrombosis and Haemostasis, 2003)
The peri- and postsurgical thromboembolic prophylaxis with low molecular weight heparins is a well established therapy regimen, but the optimum duration of prophylaxis after surgery still remains uncertain. A few studies have pointed to the fact that the thromboembolic risk of high-risk patients persists longer than the in-hospital period correlating with respective hypercoagulatory conditions. The aim of the present study was to test if a prolongation of thromboprophylaxis with the low molecular weight heparin Certoparin further reduces the rate of thromboembolism in high-risk patients after orthopedic surgery. The “Long-term Thromboprophylaxis”-Study was a multicenter, randomized, double-blind, placebo-controlled trial. 360 patients who underwent endoprothetic joint replacement or osteosyn-thesis of the lower limb were initially enrolled, all of them received prophylactically 3000 U anti-Xa of Certoparin once daily for 14 days followed by randomization to prolonged Certoparin application or to placebo up to day 42. Patients were screened for deep vein thrombosis by sonography every week. Coagulation markers (fibrin monomers and D-dimers) were determined during the course of the study.Venous thromboembolism during the prolongation period was observed in 18 patients receiving placebo versus 8 patients of the prolonged Certoparin group (12.1% versus 5.0%, intention-to-treat sample). The analysis revealed a statistically significant difference in favor of Certoparin (p=0.020), which was confirmed by per-protocol analysis (14.2% versus 5.5%, p=0.012). The differences remained significant, if analyses considered only clinically symptomatic thromboembolic events (p=0.040). Patients who developed a thrombosis showed a strong increase of coagulation markers as compared to patients without subsequent thrombosis. The respective differentiation started around 18 days before diagnosis of thrombosis. Only one minor bleeding complication was observed during prolonged Certoparin prophylaxis.The present study shows that patients after joint replacement or osteosynthesis of the lower extremities have a persisting risk to develop thromboembolic complications beyond the routine duration of thromboprophylaxis. Extended prophylaxis with Certoparin resulted in a significantly lower rate of thromboembolism and should be strongly recommended.
Keywords: Low molecular weight heparin; prolonged prophylaxis; venous thromboembolism; orthopedic surgery